STRATEGI PENGELOLAAN PENDIDIKAN DALAM MEWUJUDKAN SEKOLAH BERKUALITAS DI UPT SMP NEGERI 7 TAMBANG - Dwi Novita Fauziyah; Nur Halizah; Ratih Cahayati; Serli Kardianti; Sri Hartati; Via Aqilah Ramadhani; Sohiron (Jurnal Riset Multidisiplin Edukasi, 2026)
Education management is a crucial element in creating quality schools capable of producing graduates who meet the development needs of the era. One method of education management that focuses on improving quality is the preparation and implementation of the Medium Term Work Plan (RKJM). This research aims to outline the education management strategy implemented at UPT SMP Negeri 7 Tambang in order to achieve a quality school. The method used in this research is a descriptive qualitative approach with data collection techniques through observation, interviews and analysis of school planning documents. To ensure the validity of the data, a source triangulation technique was applied which compared the results of the three data collection methods. The research subjects consisted of school principals and teaching staff involved in preparing school programs. Research findings show that the education management strategy at UPT SMP Negeri 7 Tambang is carried out through planning based on the school's vision and mission, increasing the competence of educators and teaching staff, implementing the Independent Curriculum, strengthening character education, improving facilities and infrastructure, building partnerships with various parties, as well as implementing ongoing monitoring and evaluation. This strategy is the basis for improving the quality of education services and supporting the achievement of school targets. The success of educational management depends greatly on cooperation between all school members and related parties in carrying out programs that have been planned systematically and sustainably.